The forbidden kingdom - Angarano, Michael; Chou, Collin; Silver, Casey; Fusco, John.; Minkoff, Rob.; Li, Jet, 1963-; Cheng, Long, 1954-; Liu, Yifei; Li, Bingbing, 1976-; Lionsgate (Firm); Casey Silver Productions (Firm); Relativity Media (Santa Monica, Calif. : Lionsgate, 2008)
Jason is an American teenager who is obsessed with Hong Kong cinema and kung-fu classics. He makes an extraordinary discovery in a Chinatown pawnshop: the legendary stick weapon of the Chinese sage and warrior, the Monkey King. With the lost relic in hand, Jason unexpectedly finds himself traveling back to ancient China.
Title from container.
Full screen and widescreen.
Director of photography, Peter Pau ; editor, Eric Strand ; music, David Buckley ; production designer, Bill Brzeski ; action choreographer, Woo-Ping Yuen.
Jet Li, Jackie Chan, Collin Chou, Liu Yifei, Li Bing Bing, Michael Angarano.
MPAA rating: PG-13; for sequences of martial arts action and some violence.
DVD; Dolby Digital 5.1 surround, Dolby Digital 2.0 stereo.
Keywords: Weapons, Ancient -- China -- Drama; Quests (Expeditions) -- Drama; Kung fu -- Training -- Drama; Friendship -- China -- Drama; China -- Drama; Martial arts films; Fantasy films; Romantic comedy films; Feature films; Films for the hearing impaired; Action and adventure films